Trps1 Regulates Development of Craniofacial Skeleton and Is Required for the Initiation of Palatal Shelves Fusion - Cho, Kah Yan; Kelley, Brian P.; Monier, Daisy; Lee, Brendan; Szabo-Rogers, Heather; Napierala, Dobrawa (Frontiers in Physiology, 2019)
Trichorhinophalangeal syndrome (TRPS) is an autosomal dominant disorder resulting from heterozygous mutations of the TRPS1 gene. Common craniofacial abnormalities in TRPS patients include micrognathia, hypoplastic zygomatic arch, high arched palate, and occasionally cleft palate. Studies have demonstrated that mice with a heterozygous Trps1 mutation (Trps1+/- mice) have similar features to patients with TRPS, including high arched palates. However, mice with a homozygous Trps1 mutation (Trps1-/- mice) exhibit similar but more severe abnormalities, including cleft palate. Our study aimed to characterize the craniofacial phenotype to understand the role of Trps1 in craniofacial development and gain insight on the cleft palate pathogenesis in Trps1 deficiency. Whole mount skeletal staining revealed hypoplastic skeletal and cartilaginous elements, steep nasal slope, and missing preshenoid in Trps1-/- mice. Although several craniofacial skeleton elements were abnormal in Trps1-/- mice, the Trps1 deficiency did not appear to disrupt cranial vault development. All Trps1-/- mice presented with cleft palate. Analyses of Trps1 expression during palatogenesis detected Trps1 mRNA and protein in palatal mesenchyme and in specific regions of palatal epithelium, which suggested that Trps1 is involved in palatal fusion. Ex vivo culture experiments demonstrated that Trps1-/- palatal shelves were unable to initiate the fusion process. On the molecular level, Trps1-deficiency resulted in decreased epithelial expression of proteins involved in palatal fusion, including chondroitin sulfate proteoglycan, transforming growth factor-beta 3, Twist1, and beta-catenin. Mesenchymal expression of chondroitin sulfate proteoglycan expression was unaffected, indicating a cell type-specific mechanism of Trps1 regulation on chondroitin sulfate proteoglycan. In conclusion, we demonstrated that Trps1 is involved in the development of craniofacial skeletal elements and in the initiation of the palatal shelves fusion. Furthermore, our studies uncovered that Trps1 is required for epithelial expression of several proteins involved in the palatal shelves fusion.